Sociologia do direito made in Portugal: o contributo do CES no panorama nacional - Patrícia Branco; Paula Casaleiro; João Pedroso (e-cadernos ces)
At the beginning of the 21st century, we can observe the consolidation of the institutionalization and the beginning of the internationalization of the Portuguese sociology of law, in which the Centre for Social Studies (CES) of the University of Coimbra plays a central role, although other institutional actors begin to emerge. However, the gap between the disciplinary fields of sociology and law continues to prevail. This article traces the history of the sociology of law in Portugal in the 21st century, focusing on the role of CES, and it is divided into three parts: the first deals with the transversal issues of the sociology of law in Portugal; the second refers to the major themes that have been the subject of analysis in the last 20 years; and, finally, the third part focuses on future challenges to the field.